Biocompatibility and surface properties of hydrogenated amorphous silicon-germanium thin films prepared by LF-PECVD. (September 2019) - Huerta, F López; García, R M Woo; González, L García; May, A L Herrera; Arriaga, W Calleja; Vega, R; Soto, E
Abstract: We studied the surface morphology and biocompatibility of hydrogenated amorphous silicon-germanium (a-Si1-x Gex :H) thin films prepared by Low Frequency Plasma Enhanced Chemical Vapor Deposition (LF-PECVD). These films were deposited on a Corning 2947 glass substrate having a thickness of 3 μm, the electrical performance showed a decreased electrical resistance for low regime voltage. The root mean square (RMS) surface roughness of the films was measured by atomic force microscopy (AFM) in a non-contact mode. A biocompatibility tests was carried out using primary cultures of dorsal root ganglion (DRG) of Wistar rats. The DRG neurons were incubated for 18 hours on a-Si1-x Gex :H thin films, and subsequent electrophysiological recording was performed. These neurons displayed typical ionic currents, including a fast-inward current at the beginning of voltage clamp pulse (Na + current) and ensuing outward currents (K + current). In current clamp experiments, depolarizing current pulse injection caused typical action potential discharge of the neurons. These results confirmed the feasibility of using a-Si1-x Gex :H thin films as a biocompatible material.